2008
DOI: 10.1002/jmv.21170
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and cervical abnormalities in Nairobi, Kenya, an area with a high prevalence of human immunodeficiency virus infection

Abstract: Human papillomavirus (HPV) infection and cervical abnormalities, and their association with human immunodeficiency virus (HIV) infection were studied in 488 women who visited a health center in Nairobi. PCR-based HPV and cervical cytology tests were carried out on all participants, and peripheral CD4+ T cells and plasma HIV RNA were quantitated in HIV positive women. HIV were positive in 32% (155/488) of the women; 77% of these were untreated, and the others had been treated with anti-retroviral drugs within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
64
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 23 publications
15
64
0
2
Order By: Relevance
“…The overall prevalence of any type of HPV in the general populations of sub-saharan Africa for females with normal cytology is 21.8% (16). yamada et al (17) reported that the overall prevalence of HPV infection in the uterine cervix associated with abnormalities was 27% in Nairobi, kenya. The prevalence of HPV-16 and/or HPV-18 among invasive cervical cancer case ranges from 43.7% in senegal to 90.2% in Ethiopia (16).…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of any type of HPV in the general populations of sub-saharan Africa for females with normal cytology is 21.8% (16). yamada et al (17) reported that the overall prevalence of HPV infection in the uterine cervix associated with abnormalities was 27% in Nairobi, kenya. The prevalence of HPV-16 and/or HPV-18 among invasive cervical cancer case ranges from 43.7% in senegal to 90.2% in Ethiopia (16).…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12 It is also not dissimilar from reports from other African countries in the region, such as the Democratic Republic of Congo, where the prevalence of CIN among sex workers has been reported to be respectively 27% and 3% for HIV-infected and non-HIV-infected women. 13 Elsewhere in Africa, there have been reports that as much as half of HIV-1-infected women in the general population have CIN.…”
Section: Discussionmentioning
confidence: 41%
“…1 In the capital, Nairobi, HIV-infected women in the general population have been found to have a notably higher prevalence of cervical HPV infection than non-HIV-infected women (49% vs. 17%), together with a higher prevalence of LSIL (21% vs. 6.9%) and HSIL and cancer (5.8% vs. 0.6%). 9 Sex workers are a population subgroup at high risk for HIV and HPV infections 10 due to their participation in high-risk sexual practices (e.g., unprotected vaginal and/or anal sex), sex with multiple partners, and higher levels of symptomatic or untreated sexually transmitted infections (STIs). Longitudinal data from the East African region on cervical neoplasia among sex workers are scarce.…”
mentioning
confidence: 99%
“…9 In the present study HIV positive females withlower CD4 counts (around 100) were prone for SIL and thus appeared more likely to have severe lesions indicating low CD4 count, high HIV viral load and or infection with high-risk HPV types are associated with the presence of SIL. Yamada R et al 10 in Nairobi, Kenya, Leroy V at al 11 in Kigali, Rwanda and Parham GP et al 8 in Lusaka, Zambia also observed greater association of SIL with Human Papilloma Virus and low CD4 count.…”
Section: Discussionmentioning
confidence: 89%